Hubungan Antara Umur, Paritas, Frekuensi ANC dan Kepatuhan Mengkonsumsi Tablet Fe Terhadap Risiko Terjadinya Anemia Pada Ibu Hamil di Wilayah Kerja Puskesmas Pasir Panjang Kota Kupang - Fitria Atapukang (Jurnal Riset Multidisiplin Edukasi, 2025)
Background: Anemia is a complication of pregnancy that affects pregnancy, childbirth, postpartum, and the fetus. Anemia in pregnant women is called "potential danger to mother and child". The prevalence of anemia in pregnancy in the world is very high, especially in developing countries, including Indonesia. Anemia in pregnancy is one of the 15 global disease contributors, therefore anemia in pregnant women needs serious attention from all parties involved in health services. This study aims to determine the relationship between age, parity, ANC frequency, and compliance with consuming Fe tablets on the risk of anemia in pregnant women at Pasir Panjang Public Health Center, Kupang. Method: This type of research is observational with a cross sectional approach. The population in this study were 168 pregnant women who had anemia. The sampling technique used simple random sampling with a total sample of 63 respondents. Data analysis used simple logistic regression and multiple logistic regression. Conclusion: The results of the study showed that maternal age influenced the risk of anemia (p=0.029), parity influenced the risk of anemia (p=0.002), ANC frequency influenced the risk of anemia (p=0.026), compliance with consuming Fe tablets influenced the risk of anemia (p=0.000). This can be concluded that the risk factor for anemia in pregnant women that influences is compliance with consuming Fe tablets.